Development and preliminary testing of the Cardiac Rehabilitation Enrolment Obstacles (CREO) scale: Implications for service development - Fernandez, R.; Salamonson, Y.; Juergens, C.; Griffiths, R.; Davidson, Patricia (Elsevier, 2008)
In spite of the benefit in participating in cardiac rehabilitation (CR) programs, low participation rates are well documented. Participation rates are potentially lower in people who have undergone percutaneous coronary interventions (PCI). Assessment of the barriers to CR participation in PCI patients could provide vital information for the development of alternate strategies for coronary risk factor modification. The aim of this study was to develop and evaluate the psychometric properties of a scale to assess obstacles to cardiac rehabilitation enrolment in patients following PCI.This scale can be used as a useful tool for the early identification of patients who would not normally enrol into CR and offer them alternate strategies for health-related lifestyle modifcation.